Drug Surrenderers and Crime Statistics During the Implementation of Project Double Barrel (PDB) in the Philippines - Dio, Ryan V.; Apostol, Susan Mae G.; Madrazo, Anthony L. (International Journal of Social and Administrative Sciences, 2019)
It is a fact that criminality related to illegal drugs is, indeed, a social problem which affects the growth of the nation and every aspect of community life. This study analyzed the profile of drug surrenderers and the crime statistics in the Province of Sorsogon during the implementation of Project Double Barrel in the Philippines. It was found out that most of the drug surrenderers are from the marginalized sectors belonging to informal workers, construction workers and jobless. There was a notable decrease in the crime volume incidents during the implementation of Project Double Barrel in the province. Due to constraints in the number of police personnel, however, there is no significant difference in the crime solution efficiency (CSE) as compared to the previous year. Physical injury and theft were the highest among the recorded index crime while most of the non-index crime incidents recorded was related to vehicular traffic incidents and other violation of street laws.